I am trying to understand the proof of a Lemma from Greenberg's Algebraic Topology. It says:

Let $I$ be a directed set and $M_i$ a family of modules. Suppose that for every $i\in I$, we have $M_i=N_i\oplus P_i$. If $i\leq i'$, then we have a descomposition of the homomorphism $\phi_{i',i}:M_i\longrightarrow M_{i'}$, that is, $\phi_{i',i}=\psi_{i',i}+\rho_{i',i}$. Taking $N=\lim\limits_{\to} N_i$, $\psi_{i',i}:N_i\longrightarrow N$; and $P=\lim\limits_{\to} P_i$, $\rho_{i',i}:P_i\longrightarrow P$. Using the definition of limits, we have that, for $M=\bigcup_i \phi_i(M_i)$, there exists $\psi:N\longrightarrow M$ and $\rho:P\longrightarrow M$ verifying $\psi\psi_i=\phi_i$ on $N_i$ and $\rho\rho_i=\phi_i$ on $P_i$. In that case, the map $\psi\oplus \rho$ is an isomorphism.

The proof is:

Given $x\in M$, choose $x_i\in M_i$ such that $x=\phi_i(x_i)$. $x_i=y_i+z_i$ because $M_i=N_i\oplus P_i$. Construct the inverse $\theta(x)=(\psi(y_i),\rho(z_i)\in N\oplus P$. My problem is verifying that $\theta(x)$ does not depend on the choice of $x_i$.


There was a mistake. The inverse $\theta$ of the function $\psi\oplus\rho$ should be: $\theta(x)=(\psi_i(y_i),\rho_i(z_i))$.


Let $\phi_i(x_i) = x = \phi_j(x_j)$. Since $I$ is a direct system, there's $k \in I$ such that $i,j \le k$. Then $\phi_k \circ \phi_{k,i}(x_i) = \phi_i(x_i) = \phi_j(x_j) =\phi_k \circ \phi_{k,j}(x_j) $.

But $\psi \circ \psi_i = \phi_i$ on $N_i$ and $\rho \circ \rho_i = \phi_i$ on $P_i$. Thus, $\psi \circ \psi_i (y_i) = \psi \circ \psi_k \circ \psi_{k,i} (y_i) = \psi \circ \psi_k \circ \psi_{k,j} (y_j) = \psi \circ \psi_j (y_j)$.

The argument is analogous for $\rho \circ \rho_i$.

I'm assuming that you've already proved that $M$ is the direct limit of the $M_i$'s.

Now use the fact that direct limits takes exact sequences into exact sequences. Actually we just need that direct limits preserve kernels. Note that $\psi: N \rightarrow M$ comes from $\delta_i : N_i \rightarrow N_i \oplus P_i$ and this imply that $\psi$ is injective. Then we have that $\psi_i(y_i) = \psi_j(y_j)$. The same holds for $\rho_i(z_i)$ and $\rho_j(z_j)$.

  • $\begingroup$ You are right, there was a mistake, but not that one. $\endgroup$ – user203327 Apr 10 '16 at 9:39
  • $\begingroup$ I just noticed, The way I defined $\theta$ was assigning $M$ to $M$. Now It's adapted to the correct definition. $\endgroup$ – Garcez Apr 10 '16 at 21:33

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.